The boundaries of American political culture in the Civil War era - Neely, Mark E., Jr (Steven and Janice Brose lectures in the Civil War era., 2005)
Did preoccupations with family and work crowd out interest in politics in the nineteenth century, as some have argued? Arguing that social historians have gone too far in concluding that Americans were not deeply engaged in public life, and that political historians have gone too far in asserting that politics informed all of Americans' lives, the author of this book seeks to gauge the importance of politics for ordinary people in the Civil War era.